Comparative Assessment of Different Organic Fertilizers on the Growth Yield of Pechay (Brassica rapa chinensis.) - Alice Rivera (UNIVERSITAS PGRI MADIUN, 2026)
The growing demand for sustainable agriculture has heightened interest in organic fertilizers as eco-friendly alternatives to synthetic inputs. Organic fertilizer served as environmentally sustainable alternatives to chemical fertilizers, which, when overapplied, can adversely affect soil health, human health, and the physical environment. This study aimed to compare the effects of different organic fertilizers on the growth and yield of Brassica rapa chinensis (commonly known as pechay). Three types of organic fertilizers were examined: fish amino acid (FAA), compost, and vermicompost. The results indicated that FAA application yielded the highest growth responses in terms of stem height, leaf length, and the number of leaves, compared to the other organic fertilizers. However, analysis of variance (ANOVA) revealed no statistically significant differences among the organic fertilizers concerning these growth parameters at harvest. Conversely, a significant difference was observed in the final weight of pechay, with FAA treatment producing the heaviest plants. In terms of pest resistance, statistical analysis showed a significant difference among the organic fertilizers based on the number of damaged leaves, with vermicompost treatment exhibiting the highest susceptibility to leaf damage.These findings suggest that while all tested organic fertilizers support the growth and yield of B. rapa chinensis, FAA may be the most effective in enhancing biomass accumulation, whereas vermicompost may increase vulnerability to pest damage. Further research is recommended to explore the long-term impacts of these fertilizers on soil health and crop productivity